Side effects of using anovulatory women young peoples - Cancino Izaguirre, Heli (2015)
Since 1970 the Association of Lay Family Work, a private nonprofit entity, created with the sole purpose of promoting the family unit, performs as one of its immediate achievements, Lay Apostolate Family Program, for disseminating the concepts of Responsible Fatherhood, from the point of view of Christian morality.